Career-Driven Migration Decisions: A Holistic Perspective on Skilled Profiles Mobility from Tunisia - MEZGHANI, Zeineb; CHTARA, Mouna (Revue Internationale du Chercheur, 2025)
This paper uses an integrated explanatory framework to explore the decision-making mechanisms of highly skilled Tunisian professionals. By combining structural determinants emanating from the Push-Pull Theory and the Theory of Planned Behavior with a career ecosystem and transnational perspective, this study can provide a holistic understanding of the phenomenon of skilled migration. Based on six qualitative in-depth interviews with health professionals, professors, and IT workers, the findings confirm that career stagnation, lack of institutional support, and limited merit-based promotion are powerful push factors. On the other hand, the ability for professional growth, better working conditions, and psychological well-being abroad are strong pull factors. Identifying workplace respect and pursuit of a higher quality of life beyond material incentives as major drivers for migration, this article concludes that a migration decision is iterative, adaptive, and a continuous outcome of dynamic interaction between structural forces and personal agency along shifting career trajectories.